Co-creation in healthcare and research to improve service delivery for young people with chronic pain - Berryman, Carolyn; Starr, Tegan; Ferencz, Nicki; Coakley, Rachael (Frontiers in Medicine, 2024)
Co-creation is a valuable approach to improving healthcare by linking key stakeholders to generate innovative ideas and resolutions. A co-creation workshop was held in July 2019 involving the South Australian Pediatric Chronic Pain Service (PCPS) and stakeholders. The goal was to discuss and problem solve key challenges being faced by the newly formed PCPS service. Workshop participants engaged in three structured activities designed to help generate novel responses to PCPS challenges. Participants were encouraged to think broadly about systemic change at the hospital, community, and state-wide level, considering how a range of challenges impact clinical service delivery and patient engagement within PCPS. Qualitative data from this workshop suggest that stakeholders universally valued the existing services for youth with persistent pain, acknowledging the critical need for PCPS to continue the provision of comprehensive, multi-disciplinary and clientcentered assessments and treatments. However, there was also widespread recognition that the PCPS could not adequately meet the demands for pediatric chronic pain care in SA. This co-creation workshop generated constructive ideas and provided a launch pad for clinical and research innovation. Moreover, the co-creation workshop helped to energize key stakeholders, creating a network of engaged individuals who helped to mobilize change, improving chronic pain care across the healthcare continuum.